Enhancing Student Learning Motivation Through Interactive Augmented Reality-Based E-Modules on Global Warming - Rifa'i, Ahmad; Aviyanti, Lina; Sari, Ika Mustika; Gani, Amalia Weka; Salam, Abdul; Khairunnisah, Khairunnisah (Berkala Ilmiah Pendidikan Fisika, 2025)
The students' learning motivation in high school is still relatively low to participate in physics learning. This research aims to enhance students' learning motivation using Augmented Reality (AR)-based interactive E-Modules in physics learning on global warming materials. The method used is pre-experimental, with the design of one pretest-posttest group and analysis techniques using the Rasch stacking model. The research sample comprised 36 students in class X at Sukabumi City High School. The data collection instrument is in the form of a learning motivation questionnaire that three lecturers have validated. The analysis showed that all students experienced increased positive learning motivation. The use of AR-based interactive E-Module was able to increase the learning motivation of students in the medium category by 64% (23 students), the high category by 11% (4 students), and the low category by 25% (9 students). These findings show that AR technology in physics learning can significantly increase students' motivation to learn and increase their engagement and understanding of physics subjects. Thus, AR technology has the potential to be an effective tool in more interesting future learning methods, especially in complex subjects such as physics.